Q: T-3t plus 2t plus 4

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

75+2t=100-2t 4t=25 t=6.25 So t is 6.25 or 25/4.

Heyy, For this question, we first need to add 2t to both sides of the equation to get: 75 + 4t = 100 Now, subtract 75 from both sides of the equation to get: 4t = 25 At this time, divide both sides by 4 to get t alone and get: t = 25 / 4 OR 6.25 FINAL ANSWER = t=6.25

4

If someone in Harrisburg want a boyfriend come see me or e-mail me at ronak1997@gmail.com

Gather like terms: 3t - t = 13 - 4 ie 2t = 9 so t =4½ Check: 3t = 13½ + 4 = 17½, 4½ +13 = 17½ QED

Related questions

12(t+6)+8=4(2t-1)+2t 12t+72+8=8t-4+2t 12t-2t-8t=-72-8-4 2t=-84 2t/2=84/2 t=42

The answer is 55 + 12t.

75+2t=100-2t 4t=25 t=6.25 So t is 6.25 or 25/4.

Rearrange as: 2t2+11t+12 = (2t+3)(t+4) when factored

If you mean t(t+7) = 4(3+2t), then it is factored. If you meant solve for 't', then the solution is t = t2 - 12.

12 (t -6) + 8 4 (2t - 1)Distribute: 12t-72+8 8t-4Combine like terms: 12+-64 8tSubtract 12t from each side: -64 -4tMultiply each side by -1: 64 4tDivide each side by 4: 16 tSo t = 16

5t + 2 = 3t - 2t + 5 Collect like terms 5t - 3t + 2t = 5 - 2 4t = 3 t = ¾ Check: 5 x 3/4 = 3¾ + 2 = 5¾; 3x¾- 2x¾ + 5 = 5¾ QED

(t + 2)/3 + (t - 4)/6 (the common denominator 6) = [(t + 2)(2)]/(3)(2) + (t - 4)/6 = (2t + 4)/6 + (t - 4)/6 = (2t + 4 + t - 4)/6 = 3t/6 = t/2

Heyy, For this question, we first need to add 2t to both sides of the equation to get: 75 + 4t = 100 Now, subtract 75 from both sides of the equation to get: 4t = 25 At this time, divide both sides by 4 to get t alone and get: t = 25 / 4 OR 6.25 FINAL ANSWER = t=6.25

8t^2 - 11t - 4

4

If someone in Harrisburg want a boyfriend come see me or e-mail me at ronak1997@gmail.com